THE IMPLEMENTATION OF HAK KHIYAR IN INTERIOR PRODUCT AGREEMENTS IN BANDA ACEH CITY - Fazrul Azis; Saifuddin Sakdan; shabarullah shabarullah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2021)
The interior order transaction is one that uses the concept of istishna' contract, the price of the product is agreed upon at the beginning of the contract while the payment is made by making a panjar and paying off after the product is installed in the consumer's home. Of course, consumers always want the interior products made to be of high quality and special according to the desired shape and size, but sometimes the results of the ordered goods do not match expectations and contracts. From the substance of the problem, the focus of this thesis research is how the agreement made between the owner and the customer on ordering interior products in Kuta Raja, how the application of khiyar ru'yah on ordering interior products and how the perspective of bai' istishna' on the application of khiyar ru'yah. The purpose of writing this thesis is to find out the implementation of khiyar ru'yah on home interior order transactions in the perspective of bai' istishna' (a study on interior businesses in Kuta Raja District, Banda Aceh). This research uses descriptive analysis research method with primary data sources obtained from field research and secondary data from library research. The results of this study indicate that the agreement made by the owner and his customers in Kuta Raja is partly in writing and partly orally, and the application of the khiyar ru'yah right in interior order transactions, the seller, the customer, and the customer.